The Effect of Psychoeducation on Sexual Behavior Knowledge Among Adolescents at SMP Negeri 1 Telaga, Indonesia - Siti Fatmawaati Ali; Pipin Yunus; Nur Uyuun I. Biahimo; Andi Safutra Suraya (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Adolescent sexual behavior is a significant public health concern due to its association with sexually transmitted infections, unintended pregnancies, and psychosocial problems. Limited knowledge about reproductive health increases adolescents’ vulnerability to risky sexual behavior, highlighting the importance of effective educational interventions. This study aimed to analyze the effect of psychoeducation on adolescents’ sexual behavior knowledge at SMP Negeri 1 Telaga, Indonesia. A quantitative quasi-experimental design with a one-group pretest-posttest approach was used. The sample consisted of 38 students selected through purposive sampling. Data were collected using a structured questionnaire before and after psychoeducation intervention and analyzed using the Wilcoxon signed-rank test. The results showed an improvement in knowledge after the intervention, with the mean score increasing from 2.05 to 2.39. Statistical analysis indicated a significant effect of psychoeducation on adolescents’ knowledge (p < 0.05). Psychoeducation is an effective strategy for improving adolescents’ understanding of sexual health and can be implemented as a school-based health promotion program to support healthy behavioral development.